An exploratory study of Special Educational Needs Co‐ordinators' knowledge and experience of working with children who have sustained a brain injury. Issue 1 (February 2017) - Howe, Julia; Ball, Heather
Abstract : This research aimed to measure Special Educational Needs Co‐ordinators' knowledge of the educational implications of acquired brain injury in children and young people and whether experience of working with pupils with a brain injury or additional training impacts upon this knowledge. Data was collected within one local authority in England using an online survey. The results indicated that the respondents had high levels of uncertainty regarding the impact of a brain injury although they were more confident in those areas which related most closely to their practice. The responses suggested that experience of working with a pupil with a brain injury promoted greater knowledge than receiving training; the results, however, showed that only a minority of SENCos had received any training and those who had tended to have undertaken this independently. This suggests that there is a need for SENCos to be provided with specialist training in order to increase their understanding of the impact of acquired brain injury in children and young people.